2015
DOI: 10.1016/j.psyneuen.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Translational evidence for a role of endocannabinoids in the etiology and treatment of posttraumatic stress disorder

Abstract: Introduction Posttraumatic stress disorder (PTSD) is a prevalent, chronic, and disabling anxiety disorder that may develop following exposure to a traumatic event. Despite the public health significance of PTSD, relatively little is known about the etiology or pathophysiology of this disorder, and pharmacotherapy development to date has been largely opportunistic instead of mechanism-based. Recently, an accumulating body of evidence has implicated the endocannabinoid system in the etiology of PTSD, and targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 81 publications
0
35
0
2
Order By: Relevance
“…Although the small number of studies in humans as well as the inconsistent findings regarding immediate or prolonged effects of ECS stimulation warrant further investigation, these studies indicate that stimulation of the ECS might facilitate extinction learning in humans, too. Since exposure-based psychotherapies for PTSD rely on mechanisms of extinction learning (Anderson and Insel, 2006), it was argued whether stimulation of the ECS might augment therapeutic effects in PTSD (Neumeister et al, 2015). A preliminary randomized controlled trial indicated that treatment with a synthetic cannabinoid (mimicking the effects of THC) significantly reduces the reliving of the traumatic experiences in the form of nightmares in PTSD patients (Jetly et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the small number of studies in humans as well as the inconsistent findings regarding immediate or prolonged effects of ECS stimulation warrant further investigation, these studies indicate that stimulation of the ECS might facilitate extinction learning in humans, too. Since exposure-based psychotherapies for PTSD rely on mechanisms of extinction learning (Anderson and Insel, 2006), it was argued whether stimulation of the ECS might augment therapeutic effects in PTSD (Neumeister et al, 2015). A preliminary randomized controlled trial indicated that treatment with a synthetic cannabinoid (mimicking the effects of THC) significantly reduces the reliving of the traumatic experiences in the form of nightmares in PTSD patients (Jetly et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While administration of THC in PTSD patients might be problematic due to the associated risk of addiction and abuse, potential cognitive impairments, as well the pleiotropic effectors of THC, these studies demonstrate that targeting the ECS might be a promising avenue for PTSD treatment research. A safer and more specific way to stimulate the ECS could be the administration of fatty acid amide hydrolase inhibitors to counteract endocannabinoid degradation (Neumeister et al, 2015;Papini et al, 2015) or specific inhibitors of N-acylethanolamine acid amidase, the metabolizing enzyme of PEA and OEA (Bandiera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these data, there has been a significant interest in therapeutics development around eCB augmenting agents for stress-related neuropsychiatric disorders (see (Gaetani et al, 2009;Hill et al, 2009b;Hill and Patel, 2013c;Neumeister et al, 2015). Results of pending clinical trials with FAAH inhibitors will reveal therapeutic potential of this class of drug for stress-related psychiatric disorder, particularly PTSD and possibly major depression.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Anecdotes abound of the beneficial effects of cannabis use as a self-medication in PTSD, as do stories of adverse effects. These conflicting reports tie into an emerging realization that endocannabinoid systems are critically important for regulating stress responses, and indeed might offer novel therapeutic targets in PTSD (Neumeister et al, 2015). The question is whether blunt pharmacological actions such as global brain CB1 receptor activation, as occurs with cannabis use, might be beneficial, safe, and well tolerated.…”
mentioning
confidence: 99%